A Compendium of Modern Minimally Invasive Intracerebral Hemorrhage Evacuation Techniques. Issue 6 (18th October 2019) - Pan, Jonathan; Chartrain, Alexander G; Scaggiante, Jacopo; Spiotta, Alejandro M; Tang, Zhouping; Wang, Wenzhi; Pradilla, Gustavo; Murayama, Yuichi; Mori, Ryosuke; Mocco, J; Kellner, Christopher P
Abstract: Background: Minimally invasive intracerebral hemorrhage (ICH) evacuation has gained popularity with success in early-phase clinical trials. This procedure, however, is performed in very different ways around the world. Objective: To provide a technical description of these strategies that facilitates comparison and aids decisions in which surgery to perform, and to inform further improvements in minimally invasive ICH evacuation. Methods: Major authors of clinical trials evaluating each of the main techniques were contacted and asked to supply a case example and technical description of their respective surgeries. Results: Five major techniques are presented including stereotactic thrombolysis, craniopuncture, endoscopic, endoscope-assisted, and endoport-mediated. Techniques differ in numerous ways including the size of the cranial access, the size of the access corridor through the brain to the hematoma, and the evacuation strategy. Regarding cranial access, a burr hole is created in stereotactic thrombolysis and craniopuncture, a small craniectomy in endoscopic, and a small craniotomy in the other 2. Access corridors through the parenchyma range from 3 mm in craniopuncture to 13.5 mm in the endoport-mediated evacuation. Regarding evacuation strategies, stereotactic thrombolysis and craniopuncture rely on passive drainage from a catheter placed during surgery that remains in place for multiple days, while the other 3 techniques rely on active evacuation with suction and bipolar cautery. Conclusion: Future comparative clinical trials may identify the advantageous components of each strategy and contribute to improved outcomes in this patient population.